2005
DOI: 10.1038/sj.npp.1300877
|View full text |Cite
|
Sign up to set email alerts
|

Heritable Differences in the Dopaminergic Regulation of Behavior in Rats: Relationship to D2-Like Receptor G-Protein Function

Abstract: We reported heritable differences between Sprague-Dawley (SD) and Long Evans (LE) rats in their sensitivity to the disruption of prepulse inhibition of startle (PPI) by dopamine (DA) agonists, and in their basal levels and turnover of forebrain DA. In an effort to better understand these differences, we assessed strain patterns in the efficacy of D 2 -like receptor-G-protein coupling using [35 S]GTPgS binding in brain regions that contribute to the dopaminergic regulation of PPI. Sensitivity to the PPI-disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 26 publications
3
34
0
1
Order By: Relevance
“…For example, after localized intra-NACc AMPH infusion, SDxLE F1 rats exhibit a PPI phenotype comparable to SD rats ( Figure 4A), while systemic AMPH injection yields an F1 phenotype that is intermediate between parental strains (Swerdlow et al 2003a). We can speculate that dopaminergic changes within multiple subregions contribute to strain differences in reduced PPI after systemic drug administration, even though in isolation (after localized infusion), the contribution of any single region does not achieve statistical significance; this speculation would be consistent with our findings that differences in DA-stimulated GTPγS binding between SD and LE rats are observed not only within the NAC, but also within the AMS and cortical regions (Swerdlow et al 2006a), consistent with anatomically distributed genetically-based differences in dopaminergic function. In fact, one could argue that the strain differences observed after systemic AMPH administration are best reproduced by an (admittedly artificial) integration of AMPH effects across all of the infusion sites in the present study ( Figure 6B), although even this artificial reconstruction omits brain regions (eg.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…For example, after localized intra-NACc AMPH infusion, SDxLE F1 rats exhibit a PPI phenotype comparable to SD rats ( Figure 4A), while systemic AMPH injection yields an F1 phenotype that is intermediate between parental strains (Swerdlow et al 2003a). We can speculate that dopaminergic changes within multiple subregions contribute to strain differences in reduced PPI after systemic drug administration, even though in isolation (after localized infusion), the contribution of any single region does not achieve statistical significance; this speculation would be consistent with our findings that differences in DA-stimulated GTPγS binding between SD and LE rats are observed not only within the NAC, but also within the AMS and cortical regions (Swerdlow et al 2006a), consistent with anatomically distributed genetically-based differences in dopaminergic function. In fact, one could argue that the strain differences observed after systemic AMPH administration are best reproduced by an (admittedly artificial) integration of AMPH effects across all of the infusion sites in the present study ( Figure 6B), although even this artificial reconstruction omits brain regions (eg.…”
Section: Discussionsupporting
confidence: 86%
“…Animal studies have begun to focus on the genetics of brain substrates that regulate PPI (Arguello and Gogos 2006;Petryshen et al 2005;Shilling et al 2006;Swerdlow et al 2006a). For example, there are heritable differences in the dopaminergic regulation of PPI in both mice (Ralph & Caine 2005) and rats (Swerdlow etal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due in part to the use of different strains of rat in social isolation experiments including Lister hooded (Jones et al 1992), Fawn hooded (Djouma et al 2006), Wistar (Guisado et al 1980) and Sprague-Dawley (Del Arco et al 2004). Similarly, differences in the affinity state of the D 2 receptor have been shown using [ 35 S]GTPγS binding in different strains of rats, thus making a comparison between radioligand binding and immunohistochemistry studies problematic (Swerdlow et al, 2006). In the same strain of rats (Sprague Dawley) used in the present study, it has been reported that social isolation did not alter [ 3 H]-raclopride binding to D 2 receptors in the dorsal or ventral striatum (Del Arco et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In outbred SD, LE and F1 (SD × LE) strains, the inherited phenotype of PPI sensitivity to DA agonists is mediated by DA-linked signal transduction pathways within the ventral forebrain (Swerdlow et al 2006a;Saint Marie et al 2007). Clearly, pedigrees from different strains demonstrate different patterns of inheritance of PPI phenotypes, and the present findings demonstrate that patterns of generational transmission of the PPI APO sensitivity phenotype cannot be generalized across all rat strains.…”
Section: Discussionmentioning
confidence: 99%